(untitled) (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2020)
The research aimed to evaluate compliance with formal duties regarding Income Tax and Value-Added Tax at Thronson International of Venezuela, C.A. Theoretical references include Caballenas (2004), Moya (2012), Income Tax Law (2015), Value-Added Tax Law (2014), Organic Tax Code (2014), among others. The methodology was documentary, with a non-experimental, cross-sectional design. The instrument was a questionnaire with forty-nine (49) items, dichotomous responses (yes, no), evaluated by three (3) experts. The results showed compliance with the various norms and laws regarding formal duty fulfillment. It is recommended to keep the personnel involved updated on Income Tax and Value-Added Tax matters to avoid sanctions and strengthen the tax area.